Rethinking State Theory: Addressing Political Oligarchy and Dynastic Power in Indonesia - Alya Sherillia; Putri Naila Ramadhani; Gifa Al-Khoiri Ramadhani; Rudi Santoso (CV. Dyoqu Publishing and Management, 2026)
Background: The persistence of political oligarchy and dynastic power in Indonesia suggests that power tends to be concentrated within certain groups, even within a formally democratic system. This condition raises questions about the extent to which existing state theory remains relevant in explaining contemporary political realities. Aims: In response to this issue, this study aims to rethink state theory by examining its capacity to explain and address political oligarchy and dynastic power in Indonesia, while also identifying its theoretical limitations and exploring possible contextual reinterpretations. Methods: This study adopts a qualitative conceptual approach based on a critical review of the literature. It draws on key perspectives in political science, including state theory and elite theory, and engages with prior studies and documented political developments in Indonesia through a process of analytical synthesis. Result: The literature-based analysis indicates that conventional state theory does not fully capture the dynamics of concentrated power and the persistence of elite dominance across political generations. The presence of oligarchic structures and dynastic practices suggests that formal democratic institutions alone are insufficient to ensure an equitable distribution of power. These findings point to the need for a more context-sensitive understanding of the role and function of the state. Conclusion: Rethinking state theory offers a more grounded and contextually relevant framework for interpreting contemporary power relations in Indonesia. This study contributes to narrowing the gap between theoretical assumptions and political practice, and highlights the importance of integrating empirical realities into the analysis of the state in emerging democracies.